PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KEAKTIFAN DAN HASIL BELAJAR KIMIA SISWA KELAS X SMA YPPK AGUSTINUS KOTA SORONG - Prasetyo, Andik Karyono Dwi; Siregar, Tiurlina (Magister Pendidikan IPA, UNCEN, 2015)
This research aims to: 1. Design of learning with models of learning type Jigsaw that can be implemented more easily and attract the attention of students with learning in small groups of at least 5 persons, both in the basic group and group of experts to be able to find their own concepts so that students become skilled, active, and can improve learning achievements especially at the material of atomic structure 2. Find out the effectiveness of the application of cooperative learning, jigsaw-type model by comparing two classes of learning i.e. control class and experimental class of liveliness and learning outcomes at the material of atomic structure on grade X with their respective groups of study of 31 students. Analysis of data analysis used was normality, homogeneity, and T test so that the results of research on average N-Gain from the experimental class of 0,68 was higher compared to the control class of 0.53. It is clearly visible that the material of atomic structure is more easily to learn using the learning model jigsaw-type because the provided model learning independence of thinking and analyzing simply and not out of an existing concept so that the result is proven according to the concept. Keywords :Jigsaw-type, liveliness, outcomes, atomic structure